Current principles underlying clinician and pathologist cooperation in pathological and genetic diagnostics in breast cancer patients in the times of personalised medicine - Śrutek, Ewa; Nowikiewicz, Tomasz; Zegarski, Wojciech (Journal of Medical Science, 2018)
Positive long-term treatment outcome in cancer patients depends mainly on the disease stage. It also depends on selection of an optimum therapeutic management. In breast cancer patients, the final treatment arrangements result, to a large extent, from a quality of cooperation of medical personnel providing cancer diagnostics and therapy. This requires knowledge of mutual expectations of doctors of different specialisations. The most common problems in interdisciplinary communication are relatively easy to notice in relations between a clinician (surgeon) and a pathologist. This paper discusses the most important aspects of that relationship.